Pottery technologies and sociocultural connections btween the Aegean and Anatolia during the 3rd millenium BC (OREA, 2018)
Today archaeometric approaches to pottery are commonly utilised in Aegean Bronze Age archaeology. Pottery experts in the Aegean are now able to use various methods based on a well-established scientific framework and comparable data. This state-of-the-art interdisciplinary approach to Aegean ceramics produces a large amount of new and complex data, used by specialists and non-specialists for interpretations about socio-cultural phenomena. Therefore, the main aim of this conference volume is to bring together archaeometric experts and their scientific questions and data with traditional archaeological pottery analysis. This enables broader archaeological and cultural contextualisation within one particular geographical area and time horizon? the Early Bronze Age 1?2 periods (3000?2300 BC) on both sides of the Aegean